Deuterium-depleted water inhibits human lung carcinoma cell growth by apoptosis - CONG, FENG-SONG (D.A. Spandidos, 2010)
To investigate the in vivo and in vitro inhibitory effects of deuterium-depleted water (DDW) on human lung cancer and the possible mechanisms underlying these effects, we cultured and treated human lung carcinoma cell line A549 and human embryonic lung fibroblasts HLF-1 with various concentrations of DDW from 2 to 72 h. Cellular growth inhibition rates were determined using the 3-(4, 5-dimethyldiazol-2-yl)-2, 5-diphenyltetrazolium-bromide) (MTT) proliferation assay. A549 cells were treated with 50±5 ppm DDW, and the morphology and structure of cells were observed by scanning electron microscopy (SEM). We observed alterations in the cellular skeleton by transmission electron microscopy (TEM) and changes in cell cycle by flow cytometry. Our data showed that DDW significantly inhibited the proliferation of A549 cells at a specific time point, and cells demonstrated the characteristic morphological changes of apoptosis under SEM and TEM. The length of the S phase increased significantly in cells treated with 50 ppm DDW, whereas the G0 to G1 phase and G2 to M phase were decreased. We observed DDW-induced cellular apoptosis using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and DNA fragment analyses. In addition, we established a tumor transplantion model by injecting H460 tumor cells into subcutaneous tissue of BALB/c mice treated with DDW for 60 days. We determined the tumor inhibition rate of treated and control groups and found that the tumor weight was significantly decreased and the tumor inhibition rate was approximately 30% in the DDW group. We conclude that DDW is a promising new anticancer agent with potential for future clinical application.